2010
DOI: 10.1093/sleep/33.11.1553
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Doxepin 1 mg and 3 mg in a 12-week Sleep Laboratory and Outpatient Trial of Elderly Subjects with Chronic Primary Insomnia

Abstract: DXP 1 mg and 3 mg administered nightly to elderly chronic insomnia patients for 12 weeks resulted in significant and sustained improvements in most endpoints. These improvements were not accompanied by evidence of next-day residual sedation or other significant adverse effects. DXP also demonstrated improvements in both patient- and physician-based ratings of global insomnia outcome. The efficacy of DXP at the doses used in this study is noteworthy with respect to sleep maintenance and early morning awakenings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 29 publications
5
128
0
1
Order By: Relevance
“…15 Costs and cost-savings linked to medication are complicated by the inconsistent duration of medication use in clinical trials, even more so in the real world. A brief review of the literature found duration of clinical trials of sedative hypnotics range from short (2 weeks 16,17 ) to moderate (1-3 months [18][19][20] ) to long (6 months 15 ).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…15 Costs and cost-savings linked to medication are complicated by the inconsistent duration of medication use in clinical trials, even more so in the real world. A brief review of the literature found duration of clinical trials of sedative hypnotics range from short (2 weeks 16,17 ) to moderate (1-3 months [18][19][20] ) to long (6 months 15 ).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…In the 3-month clinical trial, the 3 mg dose produces significant improvement in sleep latency without evidence of next-day residual sedation [27] . In elderly patients, the 4-week study of 6 mg doxepin significantly improved total sleep time and sleep quality versus placebo and these improvements were sustained throughout the trial [25] .…”
Section: Low Dose Doxepin For Insomniamentioning
confidence: 99%
“…Doxepin should be avoided in patients who take anti-depresants, alcohol and sedating antihistaminic. Doxepin is metabolized by CYP isoenzymes, co-administration of cimetidine and sertraline like CYP inhibitors may increase the plasma concentration of doxepin [19,[25][26][27][28][29][30] .…”
Section: Tolerabilitymentioning
confidence: 99%
See 2 more Smart Citations